2019
DOI: 10.1002/bin.1669
|View full text |Cite
|
Sign up to set email alerts
|

Using equivalence‐based instruction to teach the visual analysis of graphs

Abstract: Previous research has demonstrated low rater agreement when visually inspecting trends in single‐subject design graphs (see Wolfe, Seaman, & Drasgow, 2016). Didactic instruction of visual analysis of practicing behavior analysts has resulted in generally poor and unreliable performances (Danov & Symons, 2008; Diller, Barry, & Gelino, 2016). Therefore, a refined instructional technology to improve the reliability among behavior analysts is warranted. Developing research has focused on the application of equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…This finding replicates Ong et al (2018) in which MTS EBI was superior to a self-instruction procedure. The finding is also consistent with prior studies that showed EBI, in general, is an effective procedure for teaching classes of verbally complex stimuli (e.g., Albright, et al, 2016a;Alter & Borrero, 2015;Blair et al, 2019;Brodsky & Fienup, 2018;Fields et al, 2009b;Fienup & Brodsky, 2017;, 2011O'Neill et al, 2015;Pytte & Fienup, 2012;Varelas & Fields, 2017;Walker & Rehfeldt, 2012). Differences in performance on generalization trials, however, were not significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding replicates Ong et al (2018) in which MTS EBI was superior to a self-instruction procedure. The finding is also consistent with prior studies that showed EBI, in general, is an effective procedure for teaching classes of verbally complex stimuli (e.g., Albright, et al, 2016a;Alter & Borrero, 2015;Blair et al, 2019;Brodsky & Fienup, 2018;Fields et al, 2009b;Fienup & Brodsky, 2017;, 2011O'Neill et al, 2015;Pytte & Fienup, 2012;Varelas & Fields, 2017;Walker & Rehfeldt, 2012). Differences in performance on generalization trials, however, were not significant.…”
Section: Discussionsupporting
confidence: 91%
“…The establishment of generalized equivalence classes is important because they demonstrate that class‐consistent responding is not restricted to only those stimuli used during training in EBI (Fields & Reeve, 2001). Similar outcomes have also been demonstrated in prior EBI studies using complex verbal stimuli with adults (e.g., Albright et al., 2016a, 2016b; Blair et al., 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To address the aforementioned limitations with using equal-interval graphs, some researchers have developed systematic protocols to aid evaluation of graphs (e.g., Wolfe et al, 2019), others have developed additional statistics or graphic aides (e.g., trend lines) to assist visual interpretation of data (e.g., Fisher et al, 2003;Lane & Gast, 2014;Lane & Sándor, 2009;Manolov & Vannest, 2019), and some suggest more intensive training (e.g., Blair et al, 2019;Nelson et al, 2017;O'Grady et al, 2018;Young & Daly, 2016). Additionally, many researchers have suggested that data should be graphed using basic principles of standardization in the construction of visual displays (e.g., Dart & Radley, 2017;Datchuk & Kubina, 2011;Kubina et al, 2017;Lindsley, 1992;Pennypacker et al, 2003;Radley et al, 2018).…”
Section: Equal-interval Graphs and Semi-logarithmic Graphsmentioning
confidence: 99%
“…Researchers have used EBI to teach definitions and applications of terms to students in higher education (see Brodsky & Fienup, 2018, for a review), including several successful applications of EBI to teach students behavior‐analytic content. Researchers have taught students behavior‐analytic terminology (Augland et al, 2020; Blair et al, 2021; Ostrosky et al, 2022), single‐subject design (Lovett et al, 2011; Walker & Rehfeldt, 2012), verbal operants (O'Neill et al, 2015), visual analysis (Blair et al, 2019), discrete‐trial teaching (Cariveau et al, 2020), and how to interpret operant functions (Albright et al, 2016). These studies collectively demonstrate that EBI consistently produces correct responding to untrained relations between stimuli.…”
mentioning
confidence: 99%